Local Residents’ and Foreign Tourists’ Intention to Participate in Ecotourism: A Research in Düden Waterfall in the Antalya City of Turkey - AKSU, AKIN; Demir, Ayşegül; İnak, Aydın; Kamış, Mahmut Doğan (Turizam, 2022)
With the help of ecotourism, it is possible to sustain environmental and cultural awareness and to decrease possible physical, behavioural impacts of touristic activities. In this study, local residents’ and foreign tourists’ intentions to participate in ecotourism practices were investigated by using attitudes towards ecotourism, likeability of tourist landscapes, intention to participate in ecotourism, and environmental knowledge ecotourism dimensions. It is seen that local residents and foreign tourists included in the sample have high averages in terms of attitude towards ecotourism, likeability of tourist landscapes, and environmental knowledge, but, have low averages in terms of their intention to participate in ecotourism. Local residents have more positive attitude towards ecotourism and higher environmental knowledge levels than foreign tourists. Female participants are more satisfied than male participants, whereas male participants have more environmental knowledge and more intention to participate in ecotourism than females.
Keywords: Residents, foreign tourists, ecotourism, Antalya, TURKEY